Hansen Solubility Parameters (HSPs): A Reliable Tool for Assessing the Selectivity of Pristine and Hybrid Polymer Nanocomposites in the Presence of Volatile Organic Compounds (VOCs) Mixtures - Enric Perarnau Ollé; Jasmina Casals‐Terré; Joan Antoni López Martínez; Josep Farré‐Lladós (Macromolecular Materials and Engineering, 2023)
Abstract Polymeric materials are widely employed for monitoring volatile organic compounds (VOCs). Compared to other sensitive materials, polymers can provide a certain degree of selectivity, based on their chemical affinity with organic solvents. The addition of conductive nanoparticles within the polymer layer is a common practice in recent years to improve the sensitivity of these materials. However, it is still unclear the effect that the nanoparticles have on the selectivity of the polymer membrane and vice versa. The current work proposes a methodology based on the Hansen solubility parameters, for assessing the selectivity of both pristine and hybrid polymer nanocomposites. The impedance response of thin polydimethylsiloxane (PDMS) films is compared to the response of hybrid polymer films, based on the addition of multi‐walled carbon nanotubes (MWCNTs). With the addition of just 1 wt.% of MWCNTs, fabricated sensors showcased a significant improvement in sensitivity, faster response times, as well as enhanced classification of non‐polar analytes (>22% increase) compared to single PDMS layers. The methodology proposed in this work can be employed in the future to assess and predict the selectivity of polymers in single or array‐based gas sensors, microfluidic channels, and other analytical devices for the purpose of VOCs discrimination.